A randomized comparative effectiveness study of oral triple therapy versus etanercept plus methotrexate in early aggressive rheumatoid arthritis: The Treatment of Early Aggressive Rheumatoid Arthritis trial - Moreland, Larry W.; O'Dell, James R.; Paulus, Harold E.; Curtis, Jeffrey R.; Bathon, Joan M.; St.Clair, E. William; Bridges Jr, S. Louis; Zhang, Jie; McVie, Theresa; Howard, George; van der Heijde, Désirée; Cofield, Stacey S. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To assess whether it is better to intensively treat all patients with early rheumatoid arthritis (RA) using combinations of drugs or to reserve this approach for patients who do not have an appropriate response (as determined by a Disease Activity Score in 28 joints using the erythrocyte sedimentation rate [DAS28‐ESR] of ≥3.2 at week 24) to methotrexate (MTX) monotherapy, and to assess whether combination therapy with MTX plus etanercept is superior to the combination of MTX plus sulfasalazine plus hydroxychloroquine. Methods The Treatment of Early Aggressive Rheumatoid Arthritis (TEAR) study is a 2‐year, randomized, double‐blind trial. A 2 × 2 factorial design was used to randomly assign subjects to 1 of 4 treatment arms: immediate treatment with MTX plus etanercept, immediate oral triple therapy (MTX plus sulfasalazine plus hydroxychloroquine), or step‐up from MTX monotherapy to one of the combination therapies (MTX plus etanercept or MTX plus sulfasalazine plus hydroxychloroquine) at week 24 if the DAS28‐ESR was ≥3.2. All treatment arms included matching placebos. The primary outcome was an observed‐group analysis of DAS28‐ESR values from week 48 to week 102. Results At week 24 (beginning of the step‐up period), subjects in the 2 immediate‐treatment groups demonstrated a greater reduction in the DAS28‐ESR compared with those in the 2 step‐up groups (3.6 versus 4.2; P < 0.0001); no differences between the combination‐therapy regimens were observed. Between week 48 and week 102, subjects randomized to the step‐up arms had a DAS28‐ESR clinical response that was not different from that of subjects who initially received combination therapy, regardless of the treatment arm. There was no significant difference in the DAS28‐ESR between subjects randomized to oral triple therapy and those randomized to receive MTX plus etanercept. By week 102, there was a statistically significant difference in the change in radiographic measurements from baseline between the group receiving MTX plus etanercept and the group receiving oral triple therapy (0.64 versus 1.69; P = 0.047). Conclusion There were no differences in the mean DAS28‐ESR during weeks 48–102 between subjects randomized to receive MTX plus etanercept and those randomized to triple therapy, regardless of whether they received immediate combination treatment or step‐up from MTX monotherapy. At 102 weeks, immediate combination treatment with either strategy was more effective than MTX monotherapy prior to the initiation of step‐up therapy. Initial use of MTX monotherapy with the addition of sulfasalazine plus hydroxychloroquine (or etanercept, if necessary, after 6 months) is a reasonable therapeutic strategy for patients with early RA. Treatment with the combination of MTX plus etanercept resulted in a statistically significant radiographic benefit compared with oral triple therapy.